Cosmological constraints on the Hu-Sawicki modified gravity scenario - Martinelli, Matteo; Melchiorri, Alessandro; Amendola, Luca (Physical review. D, Particles, fields, gravitation, and cosmology, 2009)
In this paper we place new constraints on a f(R) modified gravity model recently proposed by Hu and Sawicki (HS). After checking that the HS model produces a viable cosmology, i.e. a matter dominated epoch followed by a late-time acceleration, we constrain some of its parameters by using recent observations from the UNION compilation of luminosity distances of Supernovae type Ia, including complementary information from baryonic acoustic oscillations, Hubble expansion, and age data. We found that the data considered is unable to place significant constraints on the model parameters and we discuss the impact of a different assumption of the background model in cosmic parameters inference.